Increased Telomere Attrition After Renal Transplantation—Impact of Antimetabolite Therapy. Issue 12 (December 2016) - Luttropp, Karin; Nordfors, Louise; McGuinness, Dagmara; Wennberg, Lars; Curley, Hannah; Quasim, Tara; Genberg, Helena; Sandberg, John; Sönnerborg, Isabella; Schalling, Martin; Qureshi, Abdul Rashid; Bárány, Peter; et al.
Abstract : Background: The uremic milieu exposes chronic kidney disease (CKD) patients to premature ageing processes. The impact of renal replacement therapy (dialysis and renal transplantation [RTx]) or immunosuppressive treatment regimens on ageing biomarkers has scarcely been studied. Methods: In this study telomere length in whole blood cells was measured in 49 dialysis patients and 47 RTx patients close to therapy initiation and again after 12 months. Forty-three non-CKD patients were included as controls. Results: Non-CKD patients had significantly ( P ⩽ 0.01) longer telomeres than CKD patients. Telomere attrition after 12 months was significantly greater in RTx patients compared to dialysis patients ( P = 0.008). RTx patients receiving mycophenolate mofetil (MMF) had a greater ( P = 0.007) degree of telomere attrition compared to those treated with azathioprine. After 12 months, folate was significantly higher in RTx patients than in dialysis patients ( P < 0.0001), whereas the opposite was true for homocysteine ( P < 0.0001). The azathioprine group had lower levels of folate after 12 months than the MMF group ( P = 0.003). Conclusions: The associations between immunosuppressive therapy, telomere attrition, and changes in folate indicate a link between methyl donor potential, immunosuppressive drugs, and biological ageing. The hypothesis that the increased telomere attrition, observed in the MMF group after RTx, is driven by the immunosuppressive treatment, deserves further attention.